2002
DOI: 10.1081/cbi-120014569
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effect on Entrainment, Phase Shifting, and Amplitude of Circadian Clocks and Its Molecular Bases

Abstract: Effects of temperature and temperature changes on circadian clocks in cyanobacteria, unicellular algae, and plants, as well as fungi, arthropods, and vertebrates are reviewed. Periodic temperature with periods around 24 h even in the low range of 1-2 degrees C (strong Zeitgeber effect) can entrain all ectothermic (poikilothermic) organisms. This is also reflected by the phase shifts-recorded by phase response curves (PRCs)-that are elicited by step- or pulsewise changes in the temperature. The amount of phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
202
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(207 citation statements)
references
References 240 publications
5
202
0
Order By: Relevance
“…These and many other experiments have shown that circannual clocks, like circadian clocks (e.g. Pengelley & Fisher 1963;Aschoff 1979;Thomas et al 1993;Sawyer et al 1997;Rensing & Ruof 2002), are not entirely temperature-compensated. That is, if environmental temperatures induce changes in energy turnover in some individuals, these individuals should have faster or slower endogenous circannual clocks.…”
Section: Discussionmentioning
confidence: 99%
“…These and many other experiments have shown that circannual clocks, like circadian clocks (e.g. Pengelley & Fisher 1963;Aschoff 1979;Thomas et al 1993;Sawyer et al 1997;Rensing & Ruof 2002), are not entirely temperature-compensated. That is, if environmental temperatures induce changes in energy turnover in some individuals, these individuals should have faster or slower endogenous circannual clocks.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis seedlings respond to 4°C steps in temperature, but the lower limit of responsiveness for temperature cues has not been defined in this species. Strikingly, temperature steps of 1°C entrain the Kalanchoë circadian oscillator (35). Given the possibility of similar sensitivity for Arabidopsis, we designed our experimental system to avoid zeitgeber information arising from unintended ambient temperature cycles or cues that could drive expression rhythms and mask the underlying state of the oscillator in elf3.…”
Section: Discussionmentioning
confidence: 99%
“…Abundant evidence supports the importance of temperature cycles in clock entrainment. Temperature steps as small as 0.5°C can entrain the Kalanchoe¨clock, showing the exquisite sensitivity of the system (Rensing and Ruoff, 2002). In Arabidopsis, gene expression and cotyledon movement can be entrained by temperature cycles Salomé et al, 2002;Salomé and McClung, 2005a), but the mechanism of action is currently unknown.…”
Section: Entrainmentmentioning
confidence: 99%